Comprehensive management of osteoarthritis and hypertension in an elderly patient: a family medicine case study - Aulia, Alfira; Yasmin, Nabila Rayhan (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Osteoarthritis (OA) and hypertension are common chronic degenerative diseases in the elderly, often affecting physical function and quality of life. This case study aimed to assess a holistic management plan for an elderly male patient using the principles of family medicine. Method: This was a descriptive case study involving a 76-year-old male patient presenting with bilateral knee and ankle pain for three years and newly diagnosed hypertension. Data were collected through anamnesis, physical examination, home visits, and family assessments. Interventions included pharmacological treatment and structured non-pharmacological management with educational counseling based on patient-centred and family-focused care. Results: Pharmacological therapy included meloxicam, vitamin B12, and amlodipine. Non-pharmacological strategies focused on lifestyle modification, OA-targeted exercises, and disease education for the patient and family. Post-intervention, the patient reported reduced pain (VAS score reduced from 7 to 2), improved blood pressure (from 159/90 mmHg to 140/83 mmHg), and enhanced disease knowledge (pre-test 60% to post-test 90%). Family support and environmental factors also improved. No adverse effects or complications were observed during the intervention. Conclusion: A comprehensive family medicine approach combining medical therapy and targeted education effectively improved clinical symptoms and patient understanding in managing OA and hypertension in the elderly. These findings highlight the importance of family involvement and continuous health education at the primary care level.